Justicia pedagógica y atención a la diversidad - Lamas Ladaga, Ana María (Revista Complutense de Educación, 2006)
The attention to the diversity is understood in the Latin American countries specially in Argentina, like a debt of social justice. Within the framework of that premise, this work tries, to show relations between both concepts and the problems that are provoked when they are used with different meanings. Those general appreciations are maintained, in addition, in research. In the end we include some reflections about some possible ways to achive a right school and the practice of pedagogical justice.
Keywords: Pedagogical justice; Diversity; Difference; Complex equality; Pedagogical epimeléia